Senescence Inducer Shikonin ROS-Dependently Suppressed Lung Cancer Progression - Zheng, Hongming; Huang, Qiuju; Huang, Suchao; Yang, Xia; Zhu, Ting; Wang, Wensheng; Wang, Haojia; He, Shugui; Ji, Liyan; Wang, Ying; Qi, Xiaoxiao; Liu, Zhongqiu; et al. (Frontiers in Pharmacology, 2018)
Abstract Lung adenocarcinoma, predominant subclassfication of lung cancer, leads high incidence and mortality annually worldwide. During the premalignant transition from lung adenomas to lung adenocarcinoma, cellular senescence is regard as a critical physiological barrier against tumor progression. Nevertheless, the role of senescence in tumorigenesis is controversial and few senescence inducers are extensively determined. In this study, we used two classical cell lines A549 and H1299 and two NSCLC xenograft models on Balb/c-nude mice to reveal the pro-senescence effects of shikonin and the corresponding underlying mechanism in lung adenocarcinoma. Shikonin, a pure compound isolated from the herbal medicine lithospermum erythrorhizon, remarkably stimulated cellular senescence including increased SAHF formation, enlarged cellular morphology, and induced SA-β-Gal positive staining. Further mechanism study revealed that the pro-senescence effect of shikonin was dependent on the increased intercellular ROS generation, which subsequently triggered DNA damage-p53/p21waf axis without activating oncogenes such as Ras and MEK-1. Meanwhile, Kdm2b, an H3K36me2-specific demethylase effectively suppressed ROS generation, was also notably suppressed by shikonin treatment. Moreover, shikonin at 10 mg/kg significantly inhibited tumor weights by 55.84% and 50.98% in A549 and H1299 xenograft model, respectively (P < 0.05) through activating cellular senescence. Our study suggested that shikonin, a ROS-dependent senescence inducer, could serve as a promising agent for further lung cancer treatment.